Peran Creative Promotion, Visual Merchandising, dan Customer Experience Terhadap Pembelian Ulang Di Stuffcollection08 Palu - Nugroho, Muhammad Aqshal; Bachri, Syamsul; Rombe, Elimawaty; Evrianti, Hesti (JURNAL MANAJEMEN MOTIVASI, 2026)
This study aims to analyze the role of creative promotion, visual merchandising, and customer experience in enhancing repeat purchases among consumers of StuffCollection08 Palu. The research employs a descriptive quantitative approach, with data collected through questionnaires administered to 120 respondents using purposive sampling. Data analysis was conducted using validity and reliability tests, multiple linear regression, F-tests, and t-tests. The results indicate that all three variables have a positive and significant effect on repeat purchases, both simultaneously and partially. These findings highlight the importance of integrated marketing strategies in fostering customer loyalty and ensuring the sustainability of retail businesses.